Sistem Informasi Sales Performance Mobile Berbasis Android Pada PT. Arwana Citramulia TBK Jakarta - Yuni Eka Achyani; Ibnu Abbas (Paradigma - Jurnal Komputer dan Informatika, 2022)
PT. Arwana Citramulia. TBK is one of the manufacturing companies engaged in the sale of ceramics. PT. Arwana Citramulia. TBK already has its own ERP application but there is still a lack of a Customer Relationship Management (CRM) module, making it difficult to see sales results effectively and efficiently for each customer. Therefore, it is necessary to implement CRM to overcome these problems. The stages of implementing this CRM begin with a preliminary study. At this stage, problem identification is carried out through interviews and observations, identifying ongoing business processes and then making system proposals. The description of the system work model that is applied using a use case diagram. The next step is to select the CRM application, then configure and customize the CRM application module. The results of this study indicate that the CRM software that has been selected and implemented, namely the Sales Performance Mobile application can overcome problems at PT. Arowana Citramulia. Tbk., accompanied by the features in the mobile and web sales performance, so every marketing can be easy and effective in selling goods.